Nanoparticles of Cu–Co alloy derived from layered double hydroxides and their catalytic performance for higher alcohol synthesis from syngas. Issue 72 (6th August 2015) - Cao, Ang; Liu, Guilong; Yue, Yizhi; Zhang, Lihong; Liu, Yuan
<x xml:space="preserve">Abstract</x> A series of layered double hydroxides (LDHs) with different Cu/Co ratios were prepared according to the co-precipitation method and used as catalyst precursors for higher alcohol synthesis.